Symmetrical Fibrous Hyperplasia of the Palate - Tomislav Katanec; Ana Bakula; Irina Filipović-Zore; Tihomir Kuna (University of Zagreb. School of Dental Medicine, 2021)
Bilateral symmetrical fibrous palate hyperplasia is not a common case in the literature. The cause of this pathological change is not completely known. The development of hyperplasia may also be associated with a genetic mutation in the gingival soft tissue or gingival injury. We present a case of a 47-year-old patient who developed a formation that manifested bilaterally in the hard palate. After the excision, there were no histological elements in the material that indicated aggressive behavior of the formation. The clinical and histological diagnosis was the bilateral symmetrical palate hyperplasia, which is a very rare condition.